Shrinking projection method for solving inclusion problem and fixed point problem in reflexive Banach spaces. (2nd September 2021) - Chang, Shih-sen; Yao, J. C.; Wen, Ching-Feng; Qin, Li Juan
ABSTRACT: The purpose of this paper is to find a common element in the intersection of the set of zeros of the inclusion problem of sum of two monotone mappings and the set of fixed points of a Bregman quasi nonexpansive mapping in a reflexive Banach space by using Bregman distance and shrinking projection method. Under suitable conditions, some strong convergence theorems are proved. As applications, we utilize our results to study the convex minimization problem, variational inequality problem.